2013
DOI: 10.1016/j.jpedsurg.2013.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary bypass after severe blunt hepatic injury: management of multi-system blunt trauma in an adolescent

Abstract: A 16-year-old adolescent male sustained combined injuries to the tricuspid valve and liver. This injury is exceptional due to the mechanism and the circumstances in which it took place: a flying pumpkin thrown from a sport utility vehicle. An echocardiogram demonstrated a flail chordal apparatus associated with the posterior leaflet of the tricuspid valve, creating substrate for severe tricuspid regurgitation with preserved right heart function. He was treated with non-operative management for the liver injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…As Kaplan et al 7 ) reported, delayed hemorrhage generally occurs during the first 72 h. Repair within this period did not seem inevitable for our patient who was stable. However, Tiberio et al 8 ) reported that the median healing time of grade II subcapsular hematomas in the liver was 16 days, and Streit et al 9 ) reported tricuspid valve repair using CPB 17 days after NOM for concomitant blunt hepatic injury. Takahashi et al 10 ) also reported successful repair of an ascending aortic dissection caused by blunt trauma accompanied by multiorgan injuries 10 months after the incident.…”
Section: Discussionmentioning
confidence: 99%
“…As Kaplan et al 7 ) reported, delayed hemorrhage generally occurs during the first 72 h. Repair within this period did not seem inevitable for our patient who was stable. However, Tiberio et al 8 ) reported that the median healing time of grade II subcapsular hematomas in the liver was 16 days, and Streit et al 9 ) reported tricuspid valve repair using CPB 17 days after NOM for concomitant blunt hepatic injury. Takahashi et al 10 ) also reported successful repair of an ascending aortic dissection caused by blunt trauma accompanied by multiorgan injuries 10 months after the incident.…”
Section: Discussionmentioning
confidence: 99%